2001
DOI: 10.1002/ijc.10162
|View full text |Cite
|
Sign up to set email alerts
|

A phase I‐II study of docetaxel‐ifosfamide‐cisplatin (DIP) combination chemotherapy regimen in advanced nonsmall cell lung cancer

Abstract: In an attempt to develop more effective chemotherapy regimens in advanced nonsmall cell lung cancer (NSCLC), we evaluated docetaxel-ifosfamide-cisplatin (DIP) based on our previous experience with paclitaxel-ifosfamide-cisplatin. Patients with advanced NSCLC (stages III-IV), WHO-PS<2, no prior chemotherapy and unimpaired hematopoietic and organ function were eligible. Chemotherapy was administered in successive dose levels (DLs) and included docetaxel (80 -100 mg/m 2 day 1), ifosfamide (4 -5 g/m 2 ) and cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Based on these preclinical in vitro experimental data, we believe that the sequence and infusion times regarding docetaxel and ifosfamide, as applied in the present study, might lead to potential in vivo synergism between these two drugs (Kearns et al, 1995). Moreover, our prior experience with paclitaxel -ifosfamidecisplatin (Kosmas et al, 2000a, b;2001) or docetaxel -ifosfamide -cisplatin (Kosmas et al, 2002) combinations has demonstrated their feasibility in phase I and phase II studies in advanced solid tumours and lung cancer in particular.…”
Section: Discussionmentioning
confidence: 75%
“…Based on these preclinical in vitro experimental data, we believe that the sequence and infusion times regarding docetaxel and ifosfamide, as applied in the present study, might lead to potential in vivo synergism between these two drugs (Kearns et al, 1995). Moreover, our prior experience with paclitaxel -ifosfamidecisplatin (Kosmas et al, 2000a, b;2001) or docetaxel -ifosfamide -cisplatin (Kosmas et al, 2002) combinations has demonstrated their feasibility in phase I and phase II studies in advanced solid tumours and lung cancer in particular.…”
Section: Discussionmentioning
confidence: 75%
“…However, with a 12.5% incidence of FN for DICb compared with an average 5–6% for docetaxel-carboplatin in phase II, it appears that DICb is more myelotoxic. However, its bone marrow toxicity is far less than the 20% incidence of FN with our previous phase II study with the DIP regimen [7]. Despite the 30% incidence of grade 4 neutropenia, it can be stated that this was rarely prolonged (>7 days) and therefore, patients were unlikely to be exposed to the rigors of severe FN.…”
Section: Discussionmentioning
confidence: 96%
“…These different types of DNA lesion caused by platinum compounds and oxazaphosphorine cytostatics are repaired by the nucleotide excision repair and the mismatch repair pathways [34]. Over the last 5 years, based on the above theoretical assumptions and experimental data, we developed regimens combining a taxane, ifosfamide, and platinum compounds: initially the paclitaxel-ifosfamide-cisplatin (PIC) [35,36,37], then the DIP [7], and currently the docetaxel-ifosfamide-carboplatin (DICb) regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations